Evidence for Fgf and Wnt regulation of Lhx2 during limb development via two limb-specific Lhx2-associated cis-regulatory modules - Britton, Jessica C.; Somogyi-Leatigaga, Anett; Watson, Billy A.; Haro, Endika; Mulder, Cassidy G.; Kennedy, Kari D.; Cooper, Allen M.; Whitley, Kristen L.; Yeboah, Ruth-Love; Kim, Jeanyoung; Yu, Micah C.; Campos, Jairo D.; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionIn vertebrate limb morphogenesis, wingless-related integration site (Wnt) proteins and fibroblast growth factors (Fgfs) secreted from the apical ectodermal ridge (AER) coordinate proximodistal outgrowth. Fgfs also sustain sonic hedgehog (Shh) in the zone of polarizing activity (ZPA). Shh directs anteroposterior patterning and expansion and regulates AER-Fgfs, establishing a positive regulatory feedback loop that is vital in sustaining limb outgrowth. The transcription factor LIM homeodomain 2 (Lhx2) is expressed in the distal mesoderm and coordinates AER and ZPA signals that control cellular proliferation, differentiation, and shaping of the developing limb. Yet how Lhx2 is transcriptionally regulated to support such functions has only been partially characterized.Methods/ResultsWe have identified two limb-specific cis-regulatory modules (CRMs) active within the Lhx2 expression domain in the limb. Chromatin conformation analysis of the Lhx2 locus in mouse embryonic limb bud cells predicted CRMs-Lhx2 promoter interactions. Single-cell RNA-sequencing analysis of limb bud cells revealed co-expression of several Fgf-related Ets and Wnt-related Tcf/Lef transcripts in Lhx2-expressing cells. Additionally, disruption of Ets and Tcf/Lef binding sites resulted in loss of reporter-driven CRM activity. Finally, binding of β-catenin to both Lhx2-associated CRMs supports the associated binding of Tcf/Lef transcription factors.DiscussionThese results suggest a role for Ets and Tcf/Lef transcription factors in the regulation of Lhx2 expression through these limb-specific Lhx2-associated CRMs. Moreover, these CRMs provide a mechanism for Fgf and Wnt signaling to localize and maintain distal Lhx2 expression during vertebrate limb development.